ANALISIS KEAMANAN DATA SELULER TERHADAP SERANGAN SNIFFING MENGGUNAKAN RTL-SDR - Savitri, Yulivia Rhadita; Soim, Sopian; Fadhli, Mohammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
Data security on cellular networks is needed to maintain privacy and avoid illegal actions, because the process of communication and sending data remotely using cellular networks, especially GSM and GPRS are still widely used than conventional methods. One of the potential for sniffing data security holes can occur in the air interface, it is signalling system when transmitting data between user devices or Mobile Station (MS) and Base Transceiver Station (BTS). Therefore, to find out the quality of data security on GSM and GPRS cellular networks, a penetration testing method with RTL-SDR device are tested. The results obtained are the cellular network security system used is still secure based on data transmission patterns using timeslot, Temporary Mobile Subscriber Identity (TMSI), and changes in GSM Frame Number on GSM. Then, network security on GPRS is also still safe using logic channels, timeslot, and different security algorithm from GSM.